Effect of two freezing extenders on characteristic of fresh and frozen-thawed semen in endangered Old Kladruber stallions - A pilot study - Jiří Šichtař; Anežka Nehasilová; Ondřej Šimoník; Filipa Bubeníčková (Czech Journal of Animal Science, 2017)
The aim of the study was to evaluate the effect of two different extenders on sperm characteristic before equilibration and post-thaw in the endangered Old Kladruber stallions. Also, the response of individual stallions to the extenders used was tested. Semen was collected from six stallions every other day within one week. After centrifugation of the collected sperm-rich fraction, the supernatant was removed and sperm pellets were divided to two aliquots; these were diluted either with Gent (Minitube, Germany) or privately manufactured lactose-EDTA-egg yolk extender (Lact). Three cryopreserved insemination doses (IDs) from each extender (Gent and Lact) were prepared for each stallion from one collection (108 samples from six stallions in total). As a parameter of quality, the motility (computer assisted sperm analysis), viability (fluorescence staining), and morphology (eosin/nigrosine staining) were evaluated after dilution with freezing extenders (fresh) and after thawing (frozen-thawed). The different effects of chosen extenders on the quality of fresh semen were only manifested in higher kinematic parameters of sperm when the Lact extender was used. However, in frozen-thawed samples, the Gent extender yielded significantly better results in all of the evaluated parameters. The representation of sperm subpopulation was significantly influenced by extender in fresh as well as frozen-thawed samples; moreover, we found a significant effect of freezing on the distribution of these subpopulations. The response of individual stallions to chosen extenders was evident in the different quality of fresh as well as frozen-thawed IDs; Gent extender yielded better frozen-thawed IDs. Based on our results, among others describing quality parameters of ejaculate in endangered Old Kladruber stallions, we can recommend using Gent extender for the production of frozen-thawed IDs.